(untitled) (PAMPA, 2023)
The objective of the article was to study which public policies, at the national level, family farmers accessed during the period from 2011 to 2015, as well as the institutional support received, sustained by the perspective of rural development of rural families in Roque Gonzales, Brazil. For this, farmers and representatives of the institutions were interviewed and typification was adopted as a basis for the knowledge of the policies accessed, institutional role and development strategies. Decapitalized and in decapitalization family farmers registered less backing in policies and institutional support, while in capitalization and capitalized farmers presented better indicators. Little metamorphism will occur if farmers, institutions and managers do not adopt a proactive rationality about rural development, which will be achieved when there is a systemic synergy between the social protagonists.